Prevalence and determinants of intimate partner violence in pregnancy: a multicentre, binational study - Akaninyene E. Ubom; Chidinma P. Ohachenu; Suraiya S. Auwal; Safiyya F. Usman; Akwasi B. Opoku; Caesar A. Ansing; Jamiu S. Shehu; Peter C. Oriji; Komommo O. Okpebri; Ademola S. Olutoye; Rasheedat O. Balogun; Joshua E. Ifebude; et al. (BMC Pregnancy and Childbirth)
Abstract Background Globally, intimate partners are the most common perpetrators of violence against women. Sub-Saharan Africa (SSA) contributes significantly to the burden of intimate partner violence (IPV) in Africa, with four of every 10 women in SSA having experienced IPV. When IPV occurs in pregnancy, it is significantly associated with adverse outcomes. This study sought to assess the prevalence, determinants and complications of IPV in pregnancy in Nigeria and Ghana, two SSA countries. Methods A descriptive, cross-sectional study, conducted between February-July 2022, amongst pregnant women attending antenatal care clinics in 17 health facilities across the six geopolitical zones in Nigeria, and three hospitals in three regions in Ghana. The women were screened for IPV using an adaptation of the ‘HARK’ (Humiliation, Afraid, Rape, Kick) questions. Data obtained were analysed using the IBM SPSS Statistics for Windows, version 25. Associations between IPV and sociodemographic characteristics of the women and their spouses/partners were tested using Pearson’s Chi square. Factors found to be statistically significant were subjected to binary logistic regression modelling to determine the predictors of IPV. The level of statistical significance was set at a p-value of < 0.05. Results The prevalence of IPV was 26.2%. Predictors of IPV included the women’s marital status (p = 0.001), educational status (p = 0.040), rural residence (p = 0.034), occupation (p = 0.040), spouse’s/partner’s occupation (p = 0.021), use of illicit drugs by spouse/partner (p = 0.014), history of psychiatric illness in spouse/partner (p = 0.030), experience of IPV in previous relationship(s) by spouse/partner (p = 0.011), and witness of parental IPV by spouse/partner (p < 0.001). The most common complication of IPV in pregnancy were the mental health complications of anxiety (54.7%) and depression (46.9%). Miscarriages (15.6%) and preterm birth (9.5%) were the most common pregnancy complications. Conclusions One in every four pregnant women in Nigeria and Ghana experience IPV, with significant mental health and pregnancy complications. Routine IPV screening in pregnancy and prompt referral of screen-positive women to support services is recommended. Policies and interventions that promote gender equality and women’s economic and educational empowerment are beneficial.